Analysis of restoration in atrophic scar by intradermal autologous dermal tissue: a pilot study - Sudhir Singh; Adarsh L. Singh; Deepika Singh (Journal of the Egyptian Women’s Dermatologic Society)
Background Treating depressed atrophic scars, which can result from various causes like post-trauma, acne vulgaris, and varicella, can be challenging. Still, there are several therapeutic modalities available that can help improve their appearance. Developing a method that is easy, safe, and effective in treating depressed scars is a significant goal in dermatology and aesthetics. Objective To assess the efficacy of autologous dermal tissue transplantation in correcting atrophic scars due to trauma, acne vulgaris, varicella infection, and other inflammatory diseases and to evaluate any side effects associated with the procedure. Patients and methods Eleven patients with depressed atrophic scars willing to undergo the procedure were selected. Dermal tissue harvested after removing the epidermis by dermabrasion, was cut into small pieces, and inserted in the dermis of the recipient site with the help of 18 G needle. 2 experienced dermatologists did assessment of results by using clinical assessment scores. Results Out of 11 patients, one patient showed a 25–50% improvement, six patients showed improvement between 51 and 75%, and four patients showed more than 75% improvement. Improvement was good in small linear scars. Milia-like lesion developed in one patient. Conclusion Autologous dermal tissue transplantation is effective in depressed scars. The technique is safe, cheap, and can be mastered easily. It is important to continue conducting research and clinical trials to establish the benefits and limitations of autologous dermal tissue transplantation for depressed scars. Additionally, long-term follow-up studies can provide insights into the durability of the treatment results.